The prognostic role of circulating tumor cells in gastric cancer: A meta-analysis - Li, Zuxi; Song, Meijuan; Han, Shangjun; Jin, Chuanwei; Yang, Jing (Frontiers in Oncology, 2022)
Objective: Circulating tumor cell (Circulating Tumor Cell,CTC) is a new generation of effective markers for tumor prognosis evaluation, but their prognostic value in gastric cancer is still controversial. Therefore, this study used Meta analysis to evaluate the relationship between CTC and the prognosis of patients with gastric cancer, and further provided with evidence-based basis. Method: The databases of Pubmed, Cochrane, Embase, CNKI, WanFang Data and VIP were searched, and the cohort studies on the relationship between CTC and prognosis of gastric cancer were collected from the establishment of the database to December 26, 2021.The two researchers independently screened the literature, extracted the data and evaluated the bias risk of the included literature. The data were analyzed by Revman software (Review Manager version 5.4). Result: A total of 14 retrospective cohort studies were included, including 1053 patients. The results of Meta analysis showed that the overall survival time (OS) and progression-free survival time (PFS) of CTC positive patients were shorter than negative patients （HR=2.12, 95% CI=[1.37,3.29],P=0.0007；HR=2.54, 95% CI=[1.14,5.63],P=0.02）. According to the critical value of CTC positive, country, sample size, treatment mode and study time, the subgroup analysis showed that CTC positive was related to the shortening of OS in patients with gastric cancer. Based on the subgroup analysis of the factors such as CTC positive critical value < 2.8, sample size ≥ 75, mixed therapy, long time study and country, it was found that OS in CTC positive group was shorter than that in negative group （HR =2.54, 95% CI=[1.36,4.74],P=0.003；HR =3.09，95% CI=[1.56,6.09 ]，P=0.001；HR =2.30，95% CI=[1.17,4.52]，P=0.02；HR =2.88，95% CI=[1.44,5.74]，P=0.003；HR =2.1，95% CI=[1.36,3.24]，P=0.0008）, while the critical value of positive CTC ≥ 2.8, sample size ≥ 75, choice of treatment only for operation or non-operation, short study time and other factors were not associated with OS in patients with gastric cancer. In addition, CTC positive patients had later TNM staging （OR=3.50, 95% CI=[2.21,5.54],P＜0.00001), poorer tumor differentiation（OR=2.49, 95% CI=[1.54,4.03],P=0.0002) and earlier distant metastasis （OR=2.03, 95% CI=[1.36,3.04],P=0.0006). Conclusion： CTC can be used as a prognostic indicator of gastric cancer. Gastric cancer patients with positive CTC may have a poor prognosis.